Urban theory of/from the Global South: a systematic review of issues, challenges, and pathways of decolonization - Chakrabarti, Debapriya (Frontiers in Sustainable Cities, 2023)
Urban studies in recent decades have acknowledged that the cities of the Global South are epistemically, methodologically, and empirically different. However, the theorizations of Southern cities continue to be considered outside mainstream urban theories. In addition, there remains discrepancies and imbalance in the production of scholarships in southern cities. In addition to Southern urbanism knowledge being predominantly produced in the geographical West, scholars based in the Global South experience growing marginalization as a result of access, affordances, and knowledge production politics. With increasing discussions around the politics of visibility and institutional affiliations, this study aims to systematically map and analyze the dynamics and geography of knowledge production in the field. First, a scientometric review of this study unpacks the plethora of urban theory and related publications that theorizes the Global South and places them according to where and by whom this was published. Second, this study traces the need for urban theory and the production of knowledge following the decolonization agenda to be produced by and for the south. Finally, it closes by addressing the ways forward to progress urban theory and empirics from the south through the production and coproduction of knowledge for and by the south.